Composition Operators on Some Banach Spaces of Harmonic Mappings - Munirah Aljuaid; Flavia Colonna (Journal of Function Spaces)
We study the composition operators on Banach spaces of harmonic mappings that extend several well-known Banach spaces of analytic functions on the open unit disk in the complex plane, including the α-Bloch spaces, the growth spaces, the Zygmund space, the analytic Besov spaces, and the space BMOA.